Bamboo Diversity, Utilization and Conservation with Special Reference to West Bengal - Chakravarty, Sumit; Shukla, Gopal (Indian Forester, 2012)
Bamboo is a cultural feature of South-east Asia. No country in this region is without indigenous bamboo flora. This natural resource plays a major role in the livelihood of rural people and in rural industry. Worldwide there are more than 1,250 species under 75 genera. There are 138 species in India spread across 24 genera. In West Bengal 75 species were reported which include 49 species growing only in the Botanical Gardens. All these species are described here. Both in-situ and ex-situ conservation measures are being adopted to preserve the genetic resources of bamboos. Bamboo conservation on key areas, botanic gardens and bamboo setum of West Bengal is also discussed.